Laoag City Beach Resort Complex - Fontanilla, Christian Anthony D. (Manila : National University, 2000)
The Philippines tourism continues to grow. The numbers of the domestic and foreign visitors are increasing, so thus the pressures of the some of the country's unique natural resources.
Includes bibliographical references.
Keywords: TOURISM; BEACH RESORT COMPLEX